PENGEMBANGAN BUKU SAKU BIOLOGI BERORIENTASI MODEL INQUIRY TERBIMBING PADA MATERI SISTEM PENCERNAAN MAKANAN UNTUK SISWA SMA/MA KELAS XI - Eko Wulandari (BIOCOLONY, 2020)
This research is motivated by the still limited learning resources in SMA Negeri 7 such as: students' handbooks are limited to teacher's handbooks, books are not enough library for students to share, books can be borrowed, the borrowing time limit is only three days. Still economical use of media in learning so that the delivery of teaching materials is less attractive, teachers have not yet developed teaching materials that make pocket books. students who have learning resources consist of worksheets and text books / book packages that are obtained from the source as a source of student learning. This research is a development research that uses a 4-D model that is equipped with defining, defining, designing, and developing. In this study there were 5 validators with research subjects consisting of 34 students of class XI of SMA N 7 Merangin. This research instrument uses a questionnaire of validity and practicality questionnaire. The research data is the result of the validation and practicality of a pocket book, then analyzed with descriptive analysis. Based on the results of this study, this resulted in a product consisting of a pocket book oriented to the model, guided inquiry. The Guided Biology Pocket Book Model Guided Questions generated were declared to be very valid by the validator with the percentage of validity obtained that was 89%. The resulting Biology Handbook has also proven to be very practical by teachers and students with an average grade of 3.60 results from teacher assessments and 3.66 results that can be seen by students. The Guidance Demand Biology Oriented Guidance Model Handbook about the food digestive system material produced The Guidance Demand Biology Oriented Guidance Model Guidance based inquiry that has proven to be very valid and very practical.